Forced Money (Dwangsom) in the Indonesian State Administrative Court System and Astreinte in French Conseil d'État - Erlangga, Sandya; Disyon, Huta; Anh, Hoàng Thảo (UIN Sunan Kalijaga Yogyakarta, 2023)
The administrative court system in Indonesia shares fundamental similarities with the state administrative court system in France. This study aims to conduct a comparative analysis of the judicial systems in Indonesia and France, specifically focusing on examining the regulation of forced money penalties (dwangsom) in Indonesia. It has been around for about fourteen years since Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning the State Administrative Court (